Carbon and carbon dioxide accumulation by marandu grass under nitrogen fertilization and irrigation - Dupas, Elisângela; Buzetti, Salatiér; Rabêlo, Flávio Henrique Silveira; Sarto, André Luís (Universidade Federal de Viçosa, 2016)
ABSTRACT Nitrogen (N) is the most limiting nutrient for growth of forage grasses, especially in conditions of low water availability. Therefore, it is important to evaluate the effect of N fertilization and irrigation on the accumulation of carbon (C) and carbon dioxide (CO2) by marandu grass in the Cerrado Paulista, in the rainy and dry seasons. Experiments were conducted to evaluate N fertilization in each season, with and without irrigation. Five N rates were used (0, 50, 100, 150 and 200 kg ha-1 per cutting), using urea as N source, totaling 0, 300, 600, 900 and 1200 kg ha-1 in the rainy season and 0, 100, 200, 300 and 400 kg ha-1 in the dry season. The experiments were arranged in a split-plot randomized block design. There was no significant interaction (p > 0.05) between N and time of fertilization in the irrigated experiment. However, N promoted a quadratic effect in organic matter production (OMP), accumulation of C and CO2 by marandu grass, while there was no influence of the seasons. In the non-irrigated experiment, the interaction between N rates and seasons was significant (p < 0.05) only for the rainy season. Organic matter production and C and CO2 accumulation was greater in the rainy season than in the dry season. Irrigation provided increases of approximately 20% in C and CO2 accumulation. The use of N and irrigation increases the accumulation of C and CO2 by marandu grass, and this increase is higher during the rainy season.

RESUMO O nitrogênio (N) é o nutriente mais limitante ao crescimento de gramíneas forrageiras, principalmente em condições de baixa disponibilidade hídrica, o que justifica avaliar o efeito da adubação nitrogenada e da irrigação no acúmulo de carbono (C) e dióxido de carbono (CO2) pelo capim-marandu no Cerrado Paulista, na época das águas e da seca. Para avaliar a fertilização nitrogenada em cada época foram conduzidos experimentos com e sem irrigação. Foram utilizadas cinco doses de N (0, 50, 100, 150 e 200 kg-1 ha-1 por corte), aplicadas na forma de ureia, totalizando 0, 300, 600, 900 e 1200 kg ha-1 na época das águas e 0, 100, 200, 300 e 400 kg ha-1 na época da seca. O delineamento experimental adotado foi de blocos ao acaso em esquema de parcelas subdivididas. Não houve interação significativa (p > 0,05) entre doses de N e época de fertilização no experimento irrigado. Entretanto, o fornecimento de N promoveu efeito quadrático na produção de matéria orgânica (PMO), acúmulo de C e CO2 pelo capim-marandu, enquanto não houve influência das épocas. No experimento não irrigado a interação entre doses de N e épocas do ano foi significativa (p < 0,05) somente para a época das águas. Houve maiores PMO e acúmulos de C e CO2 no período das águas em relação ao período seco. A irrigação proporcionou incrementos de aproximadamente 20% no acúmulo de C e CO2. O uso de N e irrigação aumentam o acúmulo de C e CO2 pelo capim-marandu, e esse aumento é maior na estação chuvosa.
Acúmulo de carbono e dióxido de carbono pelo capim-marandu sob adubação nitrogenada e irrigação
Keywords: global warming; greenhouse effect; forage; Brachiaria brizantha cv Marandu; aquecimento global; efeito estufa; forragem; Brachiaria brizantha cv Marandu